Entwicklung eines benutzerorientierten Werkstattprogrammiersystems für das Laserstrahlschneiden - Kollera, Harald (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1993)
Based on an analysis of the task NC programming in a shop oriented manufacturing organization a modular programming system was designed, which is structured analogous to the task. The restrictions of and demands on the flexible manufacturing of sheet meta1 parts are considered as well. Using common modelling approaches, a data model was developed which covers the whole task from the description of the workpiece to the optimization of the NC program. Another advantage of the model is that it can easily be expanded. The main focus in the development of the programming system was put on technology planning. A method was introduced which uses relations of the nearest neighbour to reduce the computing time. With this method it is possible to combine interactive functions with automatic control mechanisms without enlarging the response time of the system. For the simulation and optimization of NC programs a module was developed which uses the data model as a basis to link NC simulation and technological functions. For instance, critical contour cuts can automatically be detected with the help of the relations of the nearest neighbour while rebuilding the model from a NC progra